Channel‐based antenna synthesis for improved in‐vehicle UWB MB‐OFDM communications. Issue 9 (5th April 2019) - Sharma, Ashwani; Garcia Zuazola, Ignacio J.; Martnez, Ramón; Perallos, Asier; Batchelor, John C.
Abstract : Ultra‐wide band (UWB) is an attractive technology for innovative in‐vehicle wireless communications requiring high data rates and multiband orthogonal frequency division multiplexing (MB‐OFDM) a suitable scheme for the accomplishment due to its high performance, low‐power and low‐cost characteristics. To contribute toward improved UWB MB‐OFDM communications inside vehicles, a channel‐based antenna synthesis technique to customise in‐vehicle UWB antennas that reduce 'blind spots' in the communication channel is proposed and presented. For the realisation, a comprehensive analysis was utilised and comprised an in‐car channel evaluation including bit‐error‐rate (BER) estimations and radiation pattern‐and‐source syntheses. The channel was measured using a standard antenna to set up the base of the experiments and the distribution of the impulse responses and signal‐to‐noise ratios in the vehicle's passenger plane shown. The currently available IEEE 802.15.3a channel models were perceived unrealistic for the in‐vehicle application and the reason for measuring the channel practically. Using these specific channel measurements, the synthesised pattern is unveiled and consequently the channel‐based antenna synthesis technique used to predict the antenna source. The antenna with optimised pattern‐and‐source showed an improved BER performance compared with the standard antenna in this application; that is, a figure of merit of 37.73% minimised 'blind spots'.